The Role of Islamic Education Teachers in Preventing Radicalism at Madrasa Aliyah - Udin Supriadi; Usup Romli; Mohammad Rindu Fajar Islamy; Muhamad Parhan; Nurti Budiyanti (Nazhruna: Jurnal Pendidikan Islam, 2021)
Radicalism is seen as dangerous for the integrity of the Republic of Indonesia. It is contradictory to Islamic values, where Islam upholds the principles of tolerance, peace, and respect for one's beliefs. Therefore, serious efforts are required from all levels of society to minimize the spread of this understanding, especially for the millennial generation. This study aims to find conceptual ideal ideas to deal with issues of radicalism through the role of (IRE) Islamic Religious Education teachers in the formal learning process at schools. This study employed a qualitative approach with a descriptive analysis method. The study was carried out in Madrasa Aliyah (Islamic Senior High School) Maarif Tanjung Sari Sumedang. Data were collected through an interview, observation, and discussion. The data were analyzed using the interactive analysis technique. Results of the study revealed that the Islamic Religious Education teacher of MA Maarif Tanjung Sari played an important role in stemming radicalism. Implementing 5 principles in the teaching-learning process is the key.